Self – destructive behaviour in the context of crisis intervention - Pilecka, Barbara (Studia Psychologica: Theoria et praxis, 2007)
The aim of the intervention in the crisis is the safeguarding of people’s lives. There are also many specific aims of the intervention in crisis. The patients who are thinking about committing suicide need special help. They don’t need a long–term psychotherapy but they must have the “live of life”. On the other side of line must be some trustworthy people, whom patients can trust and respect. The next important purpose of the intervention in crisis is evaluation of suicide risk. Other purpose of the above intervention is analysis of feelings and circumstances which are connected with suicide. It is very important that people who are thinking about suicide must be helped, not only with therapeutic means but also on the daily basis, in practical things. Finally, intervention in suicide crisis is mostly recommended to be a short directive therapy.